Unfaithful Words: Tolerance - Ferenc Ruzsa (Távol-keleti Tanulmányok)
Anyone translating religious or philosophical texts of far-away cultures is painfully aware of the impossibility of the enterprise, essentially on account of the lack of terms with near-identical meaning. However, the words are only the surface: the real problem is with the different concepts they express.